Social support and subjective assessment of psychophysical condition, health, and satisfaction with quality of life among women after pregnancy loss - Grażyna Iwanowicz-Palus (BMC, 2021)
Abstract Background The task of modern medicine is not just to heal, but also to improve the patient’s well-being and achieve non-medical goals in the therapy process that enable effective physical, mental and social functioning of the patient. Social support in difficult situations mobilizes an individual’s strength and resources to cope with problems. Research on social support and women’s condition after pregnancy loss reflects a holistic approach to the patient and is important from the perspective of increasing the level of hospital care. Objective The aim of our study was to assess the impact of social support on the psychophysical condition, health, and satisfaction with quality of life among women after miscarriage and ectopic pregnancy. Methods The cross-sectional study was carried out in a group of 500 patients after miscarriage and 110 with ectopic pregnancy, hospitalized in hospitals in Lublin (Poland). The study was conducted with the use of a diagnostic survey, comprising the Berlin Social Support Scales (BSSS) and an original survey questionnaire (psychophysical condition, satisfaction with health and quality of life on a scale of 1–4, sources of support on a scale of 1–10, with 1 being the poorest rating). Results Respondents after miscarriage and those after ectopic pregnancy assigned the highest scores to the degree of perceived available instrumental support (respectively, miscarriage: M = 3.79, EP: M = 3.77). Women after pregnancy loss assigned the highest score to the support obtained from their partner (respectively, miscarriage: M = 9.26, EP: M = 9.23). Social support was significantly correlated with the condition of patients hospitalized as a result of pregnancy loss (p < 0.05). The assessment of psychophysical condition, health, and QoL of the respondents is determined by their education, financial standing, and obstetric history (p < 0.05). Conclusions Women hospitalized due to miscarriage and ectopic pregnancy assigned high scores to the level of perceived available instrumental, emotional, and actually received social support. There is a positive relationship between social support and subjective opinion about psychophysical condition, health and satisfaction with quality of life among women after pregnancy loss. The assessment is determined by sociodemographic factors and the respondents’ obstetric history.